Prenuptial Agreement Terhadap Perkawinan Campuran: Suatu Kajian Perspektif Hukum Di Indonesia - Fitri, Winda; Elviani, Elviani (Jurnal Komunikasi Hukum, 2021)
This research discusses the scope of prenuptial agreement enforcement and legal protection for the parties that involved in mixed marriages in the event of a cancellation of the prenuptial agreement. The research method used in this article is normative research with a statutory approach and a case approach, with a case study data collection technique, which produces secondary data made from primary, secondary and tertiary law. As well as using the theory of legal protection by Satjipto Rahardjo. The results article is a prenuptial agreement plays an important role in mixed marriages in protecting the rights of parties of mixed marriages. However, in the preparation of a prenuptial agreement, there are also conditions that must be fullfiled by the parties. If there has been an agreement, but it is not fulfill the requirement, then the prenuptial agreement can be canceled, in which the agreement will be assumed its never existed and the rules that were arranged will be returned to to the provisions before agreement was made